Respuesta :
Answer:
[tex] a_{1+1}= a_2 = -4 + 3 = -1[/tex]
So the second term of the sequence is -1
Step-by-step explanation:
For this case the nth term of the sequence is given by:
[tex] f(n+1) = f(n) +3[/tex]
And we can also write this like: [tex] a_{n+1} = a_n +3[/tex]
And we know that [tex] a_1 = -4[/tex]
And we are interested in find [tex] a_2[/tex] so we just need to replace n=1 into the original formula and we got:
[tex] a_{1+1}= a_2 = -4 + 3 = -1[/tex]
So the second term of the secuence is -1